Bone Marrow-Derived Mononuclear Cell Therapy in Papain-Induced Experimental Pulmonary Emphysema - Machado, Mariana N.; Mazzoli-Rocha, Flavia; Casquilho, Natália V.; Maron-Gutierrez, Tatiana; Ortenzi, Victor H.; Morales, Marcelo M.; Fortunato, Rodrigo S.; Zin, Walter A. (Frontiers in Physiology, 2018)
Murine papain-induced emphysema is a model that reproduces many of the features found in patients. Bone marrow-derived mononuclear cells (BMMC) have already been used to repair the alveolar epithelium in respiratory diseases, but not in the papain model. Thus, we hypothesized that BMMC could prevent the pathophysiological processes in papain-induced experimental emphysema. Female BALB/c mice received intratracheal instillation of 50 µL of saline (S groups) or papain (P groups, 10 IU/50 µl of saline) on days 1 and 7 of the experimental protocol. On the 14th day, 2x106 BMMC of male BALB/c mice (SC21 and PC21) or saline (SS21 and PS21) were injected by the jugular vein. Analyses were done on days 14 (S14 and P14) and 21 (SS21, PS21, SC21 and PC21) of the protocol. qPCR evaluated the presence of the Y chromosome in the lungs of BMMC recipient animals. Functional residual capacity (FRC), alveolar diameter, cellularity, elastic fiber content, concentrations of TNF-α, IL-1β, IL-6, MIP-2, KC, IFN-γ, apoptosis, mRNA expression of the dual oxidase (DUOX1 and DUOX2), production of H2O2 and DUOX activity were evaluated in lung tissue. We did not detect the Y chromosome in recipients’ lungs. FRC, alveolar diameter, polymorphonuclear cells (PMN) and levels of KC, MIP-2 and IFN-γ increased in P14 and PS21 groups; the changes in the latter were reverted by BMMC. TNF-α, IL-1β e IL-6 were similar in all groups. The amount of elastic fibers was smaller in P14 and PS21 than in other groups, and BMMC did not increase it in PC21 mice. PS21 animals showed increased DUOX activity and mRNA expression for DUOX1 and 2. Cell therapy reverted the activity of DUOX and mRNA expression of DUOX1. BMMC reduced mRNA expression of DUOX2. Apoptosis index was elevated in PS21 mice, which was reduced by cell therapy in PC21. Static compliance, viscoelastic component of elastance and pressure to overcome viscoelasticity were increased in P14 and PS21 groups. These changes and the high resistive pressure found on day 21 were reverted by BMMC. In conclusion, BMMC showed potent anti-inflammatory, antiapoptotic, antioxidant and restorative roles in papain-triggered pulmonary emphysema.